The Role of Halal Oracle Systems in Ensuring Shariah Compliance in Islamic Blockchain Applications - Nisa, Rifqun; Cholil, Ahmad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The rapid adoption of blockchain technology in Islamic finance highlights the urgent need for mechanisms that ensure every transaction, data input, and automated process remains compliant with Shariah principles. A critical component in achieving this compliance is the oracle system, which connects off-chain data to blockchain networks. However, conventional oracles often lack ethical filters, resulting in potential misalignments with Islamic law. This study conceptualizes the Halal Oracle system, a solution that integrates technical precision with Shariah governance. Using a descriptive qualitative method based on literature review, this paper examines the operational framework of Halal Oracles, contrasts them with conventional models, and explores their applications in Islamic digital sectors such as halal supply chains, digital zakat, and Shariah-compliant smart contracts. The findings indicate that Halal Oracles incorporate layers of curation, certification, and auditing based on Islamic jurisprudence, thereby reinforcing accountability and legitimacy within Islamic blockchain ecosystems. The study also highlights challenges including the need for regulatory standardization, technical interoperability, and cross-jurisdictional alignment.